Prejudice, Does It Exist or Not? Consumer Price Discrimination in Minority Entrepreneurship - Liu, Feng; Liao, Xin; Ming, Cuiqin (Frontiers in Psychology, 2020)
Many prior studies on minority entrepreneurship have found that some consumers display a strong bias against products from minority ventures. Not surprisingly, discrimination against products sold by minority-owned businesses increases the failure rate for such ventures. This paper seeks to verify the extent of consumer discrimination for minority products, and investigates whether it varies among different products. Building on insights from the theory of consumer discrimination, we conducted a comparative behavior experiment on 155 subjects for the expected pricing of two new products (common products and products with ethnic characteristics). Consistent with prior literature, we found that potential consumers held a bias against common products from minority ventures and offered a lower price. However, the theory of consumer discrimination could not be applied to the products with ethnic characteristics. Instead, potential consumers viewed ethnic characteristics products from minority ventures as being high quality and offered higher prices. This finding complements the theory of consumer discrimination and provides useful knowledge for minority entrepreneurs: minority entrepreneurs can employ price discrimination to strengthen the ethnic brand’s impression by integrating ethnic cultural features into new products.